Application of Green Accounting and Tax Avoidance to the Financial Performance of the Mining Sub-Sector (listed on the IDX) - Jessica; Susan Grace Nainggolan (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
In the era of the 4.0 industrial revolution, economic growth has experienced quite rapid development in the company's operational activities. An impact generated by a company will issue risks that affect the business and performance carried out by the company's activities, namely the company's activities towards environmental problems. The application of green accounting will encourage companies to minimize environmental problems that occur. Tax avoidance is an effort to avoid taxes that is carried out legally and safely for taxpayers because it does not conflict with tax provisions. The implementation of prolonged Tax Avoidance practices can reduce the value of the company. This study aims to determine whether Green accounting and tax avoidance have a significant effect on financial performance in mining sub-sector companies (listed on the IDX). This study uses a purposive sampling method and the data source is secondary data. The data collection technique uses the Indonesia Stock Exchange (IDX) which releases the financial statements of mining sub-sector companies for the period 2018-2023. Data analysis and testing consist of validity tests, reliability tests, descriptive statistical tests, classical assumption tests, multiple regression analysis, partial hypothesis testing (T test) and simultaneously (F test), and coefficient of determination tests. The results of this study show that Green Accounting has a significant effect partially on Financial Performance with a t count of 5,584 > t table 1.70113. Tax Avoidance did not have a significant effect on Financial Performance simultaneously with t calculation -2,692 < t table 1.70113. Green Accounting and Tax Avoidance had a significant effect simultaneously on Financial Performance with a value of 15,978 > table f 3.35 and a regression coefficient value of 54.2%.